Communication in the arts : An understanding of interpretation and appreciation of the art - Wan Abdullah Thani, W.J.I (Universiti Malaysia Sarawak, 1998)
2nd Colloquium on UNIMAS Contributions to Research 1998 Universiti Malaysia Sarawak